ENHANCING PUBLIC SERVICE DELIVERY THROUGH BLOCKCHAIN TECHNOLOGY: A NOVEL APPROACH TO TRANSPARENT AND EFFICIENT GOVERNANCE - Maolani, Dedeng Yusuf (Alqaprint Jatinangor, 2024)
Public service delivery has long faced challenges related to transparency, efficiency, and accountability. The integration of blockchain technology presents a novel solution to these issues, promising enhanced governance through secure, transparent, and efficient processes. This literature review explores the potential of blockchain technology in transforming public service delivery. It synthesizes existing research on the application of blockchain in public administration, highlighting key benefits such as improved transparency, reduced fraud, and increased efficiency. Additionally, the review identifies critical success factors and challenges in implementing blockchain-based solutions in the public sector. By examining case studies and theoretical frameworks, this study provides a comprehensive understanding of how blockchain can revolutionize public governance. The findings offer valuable insights for policymakers and practitioners aiming to leverage blockchain technology to enhance public service delivery and achieve better governance outcomes.